Pengaruh Leader-Member Exchanges, Kepuasan Kerja, Persepsi Dukungan Organisasi Terhadap Kinerja Karyawan Dengan Peran Komitmen Organisasi Sebagai Variabel Pemediasi - Achmad Yusuf Prasetyo; Jati Waskito (JURNAL LENTERA BISNIS, 2023)
This study aims to analyze the influence of leader member exchanges, perceptions of organizational support and job satisfaction on employee performance with organizational commitment as a mediator. Research using quantitative research methods. The population used was 71 respondents with subjects being BPJS Health employees in the city of Surakarta. Sampling in this study using non-probability sampling with saturated sampling technique. Data collection was carried out by distributing questionnaires to all BPJS Kesehatan employees in Surakarta. Using SmartPLS as a data analysis tool. Testing the data used includes the outer model and inner model. The findings from this study found that Leader member exchanges had no effect on organizational commitment. Leader member exchanges have a significant effect on employee performance. Perceived organizational support has a significant positive effect on organizational commitment. Perceived organizational support has no significant effect on organizational performance. Job satisfaction has a significant positive effect on organizational commitment. Job satisfaction has no significant effect on employee performance. Organizational commitment has a significant positive effect on employee performance. The role of organizational commitment as a mediator is not able to have a significant effect on the effect of leader member exchanges on employee performance. The role of organizational commitment as a mediator is able to provide a positive and significant effect on the influence of perceived organizational support on employee performance. The role of organizational commitment as a mediator is able to provide a positive and significant effect on the effect of job satisfaction on employee performanceKeywords: Leader Member Exchanges, Perceived Organizational Support, Job Satisfaction, and Employee Performance